The Analysis of Small RCS Target Detection in Primary Radar System - Vlasák, Václav; Pidanič, Jan (Croatian Society Electronics in Marine - ELMAR, 2016)
This paper describes the challenges of detecting small-RCS targets using current generation primary radar systems. The Unmanned Aerial Vehicle and drones are representative of small-RCS targets which pose serious safety issues these days. The current generation primary radar systems do not have sufficient detection, resolution and classification capabilities to detect such targets. We present an innovative signal processing chain that would help primary radar systems to detect such low-RCS targets.
Problematika detekce cílů s malou odraznou plochou v primárních radarových systémech
Keywords: primary radar systém; signal processing; dron; UAV; dectection of target; classification of target; RCS